1983
DOI: 10.1007/bf01386357
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of glycoenzymes by means of their glycosidic components

Abstract: SUMMARYGlucose oxidase was immobilized on modified glycidyl methacrylate carriers after periodate oxidation of its glycosidic component either by a direct reaction of the formed aldehyde groups with amino groups of the carrier or using a modified four-component Ugi's reaction. The conjugates formed by the latter reaction exhibited higher activity and efficiency of immobilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…In an early report of enzyme immobilization, Marek and co-workers enhanced the catalytic activity of glucose oxidase by binding it on the surface of the modified glycidyl methacrylate polymers through Ugi-4CR approach. 128 For this purpose, the glycoenzyme was reacted with periodate to prepare aldehyde groups in the glycosidic part and then participated in Ugi-4CR with amino-functionalized glycidyl methacrylate polymers, excess acetic acid and cyclohexyl isocyanide. Notably, the Ugi product showed higher activity than those products which prepared by the direct binding between the aldehyde groups and the amino groups of the polymeric carrier.…”
Section: Acs Combinatorial Sciencementioning
confidence: 99%
“…In an early report of enzyme immobilization, Marek and co-workers enhanced the catalytic activity of glucose oxidase by binding it on the surface of the modified glycidyl methacrylate polymers through Ugi-4CR approach. 128 For this purpose, the glycoenzyme was reacted with periodate to prepare aldehyde groups in the glycosidic part and then participated in Ugi-4CR with amino-functionalized glycidyl methacrylate polymers, excess acetic acid and cyclohexyl isocyanide. Notably, the Ugi product showed higher activity than those products which prepared by the direct binding between the aldehyde groups and the amino groups of the polymeric carrier.…”
Section: Acs Combinatorial Sciencementioning
confidence: 99%
“…While the Ugi reactionh as been the objecto fe xtensive studies for the conjugation and stapling of peptides, only ah andful of publications report the use of proteins as coupling partners. [32][33][34][35][36] Most notably,a ll these strategies use the four-component version of the Ugi reaction (U-4CR); that is, they only target as ingle site at the protein surface, whether it be an amino acidr esidue (lysines or aspartates/ glutamates) or aldehydes from the glycanp ortion after periodate oxidation, and the approach necessitates the use of av ast excesso fr eagents (up to 4000 equivalents) and long reaction times (up to 4days). In addition, the absence of detailed analytical investigations precludes the conclusiont hat the Ugi reaction, and not an uncontrolled side reaction, wasi ndeed responsible for the bioconjugation.…”
Section: Introductionmentioning
confidence: 99%
“…A solution of hydroxylamine would then simply be added at the end of the reaction to regenerate the amino groups of these lysine residues that did not partake in the multicomponent reaction. While the Ugi reaction has been the object of extensive studies for the conjugation and stapling of peptides, only a handful of publications report the use of proteins as coupling partners [32–36] . Most notably, all these strategies use the four‐component version of the Ugi reaction (U‐4CR); that is, they only target a single site at the protein surface, whether it be an amino acid residue (lysines or aspartates/ glutamates) or aldehydes from the glycan portion after periodate oxidation, and the approach necessitates the use of a vast excess of reagents (up to 4000 equivalents) and long reaction times (up to 4 days).…”
Section: Introductionmentioning
confidence: 99%
“…In 1983, Vodrážka et al applied Ugi reaction to immobilize glucose oxidase on a polymer carrier which was the earliest report of protein bioconjugation based on MCR ( Marek et al, 1983 ). In 2000, Lang et al reported that the Ugi reaction was used to achieve the binding of bovine serum albumin (BSA) with isocyano-modified β-D-glucosyl groups ( Ziegler et al, 2000 ).…”
Section: Strategy 2: Isocyanide-based Mcrmentioning
confidence: 99%